UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MURID PADA MATERI BANGUN RUANG KELAS VI SD INPRES BISARA MELALUI PEMBELAJARAN BERBASIS APLIKASI AUGMENTED REALIATY (AR) - Hairuddin, Hairuddin (Jurnal Analisis Pendidikan Sosial, 2024)
This research aims to find out the increasing activeness of students learning in mathematic through the media of Augmented Reality (AR) in geometry subjects. This study is a class action study with the research subjects of grade VI students SD Inpres Bisara as many as 22 people. This research was conducted 2 cycles, each cycle consisting of 2 meetings. At each meeting consists of 4 stages namely planning, implementation, observation and reflection. Data collection techniques used include interviews and observations. Based on the results of the study, in cycle I obtained an average student learning activity of 66% with enough categories. while in cycle II, the average learning activity of students is 81.2% with a high category. Thus, from cycle I and cycle II there was a 14.06% increase in student activity. thus it can be concluded that through the media of Augmented Reality (AR) can increase the active learning of grade VI students of SD Inpres Bisara towards geometry lessons.